ANALYTICAL STUDY OF THE FISHERIES IN THE LOWER REACHES OF THE TIGRIS RIVER, NORTH QURNA, BASRAH, IRAQ - MOHAMED, A. R. M.; AL-NOOR, S. S.; FARIS, R. A. K. (Iraqi Journal of Aquaculture, 2022)
The fisheries of the lower reaches of Tigris river, north Qurna in Basrah Governorate have been analyzed during the period from January to December 2005. The fishing boats used there varied in lengths form 5 to 10m, of which 50% were motorized with 25-75 HP. Seine and drift gill nets are the main fishing gears used, their lengths ranged from 100 to 200m with mesh sizes of 14-100mm and 7-32mm for seine and gill nets respectively. The number of fishermen in each boat varied from 1 to 7. Twenty three fish species were recorded caught in the area, of which eight were marine species, belonging to twelve fish families, in addition to shrimps. The total catches ranged from 629Kg in January - march to 3335Kg in July- September with total catch of 7671Kg. Three species namely catfish Silurus triostegus, crucian carp Carassius carassius and khishni Liza abu comprised 86.93% of the total catches constituting 69.65%, 11.02% and 6.26%, respectively. The average catch per unit of effort was 19.8 Kg/hr/100m for seine nets and 2.42 Kg/hr/100m for gill nets. The diversity and evenness indices for biomass were 1.0 and 0.33, respectively, in July-September and 1.5 and 0.52, respectively, in October-December. The highest similarity index of species composition was between April-June and July-September (87%), and lowest between April-June and January-March (63%).